BUILDING A CREATIVE AND EFFECTIVE BUSINESS TEAM AT BINA AMANAH CORDOVA ENTREPRENEURSHIP SCHOOL - Soekapdjo, Soeharjoto; Rustam, Rinaldi; Leila Yusran, Husna; Aryani Tribudhi, Debbie; Ratnawati, Nirdukita (LPPM Univ. Ibn Khaldun Bogor, 2022)
A solid team supports the successful development of Micro, Small, and Medium Enterprises. For this reason, Community Service is carried out with the aim that business actors can form creative and efficient teams. This activity was carried out in the Diploma Program of the Bina Amanah Cordova School of Entrepreneurship with students as participants. The method used is counseling and training, which is carried out using a two-way system, namely through the provision of material followed by discussion. The activity went smoothly and was successful because it was to the agenda that had been set. This Community Service increases the knowledge and skills of partners in forming creative and efficient teams. After participating in the activity, partners can create several strategy models and perform simulations to form a solid team. Partners and various related parties contribute by providing input so that this activity can be carried out continuously by increasing the duration of the time, but the material provided is by the case that is currently trending and adapted to the needs of its partners.